Trait Extraversion and Dopamine Function. Issue 6 (June 2015) - Wacker, Jan; Smillie, Luke D.
Abstract An influential theory within personality neuroscience suggests that trait extraversion is underpinned by individual differences in dopamine function. In a review of the relevant literature, we evaluate this theory in light of the evidence from molecular genetics, neuroimaging, and psychopharmacology. Evidence linking individual differences in extraversion with dopamine‐relevant genes, structural volume of dopamine‐rich brain regions (e.g., in striatal and ventral prefrontal areas), dopamine receptor availability, and frontal alpha asymmetry is mixed at best. Evidence concerning both scalp recorded (electroencephalogram) and hemodynamic (functional magnetic resonance imaging) neural responses to rewards appears somewhat more promising. Perhaps the best evidence concerns extraversion‐dependent responses – both neural and behavioural – to dopaminergic drugs. Future research in this area must go beyond the demonstration of theoretically consistent associations and attempt to provide more specific causal evidence for the dopamine hypothesis of extraversion. A further challenge is to expand this hypothesis to incorporate other neurobiological processes that are likely to underlie this trait.